SEGMENTAL DAN SUPRA SEGMENTAL DALAM KIDUNG MALAT COWAK DI DESA PADANGBULIA - I Gusti Made Swastya Dharma Pradnyan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2017)
Malat Cowak a traditional literary works shaped hymn often sing Padangbulia society. This kidung serves as a companion religious ceremonie’s such as, pitra yadnya and manusia yadnya. But when song, chants significant they can only be interpreted by readers based on the dictionary meaning only. As an active reader, a work of literature, especially the kidung, various kinds of theories and methods in the process of interpretation of the meaning. One way is to analyze the sound system that ties each end of words in one verse. Study of the sound system in linguistics is based on the study of phonology. Science that examines the sound system can be done with two analysis: analysis of segmental and suprasegmental.